Osteopathic and chiropractic for manual therapists : a comprehensive guide to full body spinal and peripheral manipulations /: a comprehensive guide to full body spinal and peripheral manipulations. (2017) - Michael, Jimmy; Gyer, Giles; Davis, Ricky
No abstract available